2016
DOI: 10.1007/s00431-015-2688-0
|View full text |Cite
|
Sign up to set email alerts
|

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children’s anxiety and pain levels in emergency department

Abstract: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 22 publications
3
65
0
11
Order By: Relevance
“…Among the 28 included studies, 18 are randomized prospective and controlled studies and 14 of them have parallels groups design (clowngroup/control-group) [9][10][11][12][13]16,17,[21][22][23][28][29][30]34]. Half of the studies have a sample size of less than 30 patients per group [9,11,13,14,16,18,21,23,29].…”
Section: Methods Evaluation Studies Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 28 included studies, 18 are randomized prospective and controlled studies and 14 of them have parallels groups design (clowngroup/control-group) [9][10][11][12][13]16,17,[21][22][23][28][29][30]34]. Half of the studies have a sample size of less than 30 patients per group [9,11,13,14,16,18,21,23,29].…”
Section: Methods Evaluation Studies Designmentioning
confidence: 99%
“…Over half of the studies reported intervention benefits of hospital clown for children and their parents [5,[11][12][14][15]18,[23][24][25][26]28,[31][32][33][34]. Four other studies have evaluated in addition the opinions of health professionals [4,10,13,16]. One study targeted only mother's anxiety [9].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a clown has been found to reduce the child’s anxiety (Dionigi, Sangiorgi, & Flangini, 2014; Felluga et al, 2016; Goldberg et al, 2014; Kocherov et al, 2016; Meiri, Ankri, Hamad-Saied, Konopnicki, & Pillar, 2016; Messina et al, 2014; Vagnoli, Caprilli, & Messeri, 2010; Vagnoli, Caprilli, Robiglio, & Messeri, 2005; Weintraub et al, 2014) and feelings of boredom, loneliness and sadness (Finlay, Baverstock, & Lenton, 2014; Mansson, Elfving, Petersson, Wahl, & Tunell, 2013; Meiri et al, 2016). Also, a few studies showed that a clown intervention is able to reduce anxiety in parents (Agostini et al, 2014; Fernandes & Arriaga, 2010; Wolyniez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%